A new analytical framework of 'continuum of prevention and care' to maximize HIV case detection and retention in care in Vietnam - Fujita Masami; Poudel Krishna C; Do Thi Nhan; Bui Duc Duong; Nguyen Van Kinh; Green Kimberly; Nguyen Thi Minh Thu; Kato Masaya; Jacka David; Cao Thi Thanh Thuy; Nguyen Thanh Long; Jimba Masamine (BMC, 2012)
Abstract Background The global initiative 'Treatment 2.0' calls for expanding the evidence base of optimal HIV service delivery models to maximize HIV case detection and retention in care. However limited systematic assessment has been conducted in countries with concentrated HIV epidemic. We aimed to assess HIV service availability and service connectedness in Vietnam. Methods We developed a new analytical framework of the continuum of prevention and care (COPC). Using the framework, we examined HIV service delivery in Vietnam. Specifically, we analyzed HIV service availability including geographical distribution and decentralization and service connectedness across multiple services and dimensions. We then identified system-related strengths and constraints in improving HIV case detection and retention in care. This was accomplished by reviewing related published and unpublished documents including existing service delivery data. Results Identified strengths included: decentralized HIV outpatient clinics that offer comprehensive care at the district level particularly in high HIV burden provinces; functional chronic care management for antiretroviral treatment (ART) with the involvement of people living with HIV and the links to community- and home-based care; HIV testing and counseling integrated into tuberculosis and antenatal care services in districts supported by donor-funded projects, and extensive peer outreach networks that reduce barriers for the most-at-risk populations to access services. Constraints included: fragmented local coordination mechanisms for HIV-related health services; lack of systems to monitor the expansion of HIV outpatient clinics that offer comprehensive care; underdevelopment of pre-ART care; insufficient linkage from HIV testing and counseling to pre-ART care; inadequate access to HIV-related services in districts not supported by donor-funded projects particularly in middle and low burden provinces and in mountainous remote areas; and no systematic monitoring of referral services. Conclusions Our COPC analytical framework was instrumental in identifying system-related strengths and constraints that contribute to HIV case detection and retention in care. The national HIV program plans to strengthen provincial programming by re-defining various service linkages and accelerate the transition from project-based approach to integrated service delivery in line with the 'Treatment 2.0' initiative.